Corporate Criminal Liability Against Biological Natural Resources and Ecosystems - Jazau Elvi Hasani (University of Jember, 2020)
Indonesia has various natural resources, including a diversity of natural and biological wealth. Article 33 paragraph (3) of the 1945 Constitution outlines that the state should control natural resources for national prosperity. In the context, biological natural resources can appropriately situate with the conservation effort so that the government plays a vital role in maintaining biological natural resources and their ecosystem. The development of biological natural resources and their ecosystems is essentially an integral part of sustainable national development, and efforts to conserve biological natural resources and their ecosystems are realized by analyzing and evaluating the existing legislation. This paper aims to discuss the corporate criminal liability in Indonesia in the conservation of biological natural resources and their ecosystem. Then, it suggests the possible revisions regarding the biological national resources laws. Revision of the Act on the conservation of biological natural resources has started since 2018 as it is prioritized under the national legislation program. As the revision put the crucial part of the legal creation, the protection of biological natural resources and their ecosystem becomes the government's primary concern because the existing regulation still has no deterrent effect. KEYWORDS: Corporate Criminal Liabilities, Biological Natural Resources and Ecosystems, Crime.